2017
DOI: 10.1038/s41598-017-09862-2
|View full text |Cite
|
Sign up to set email alerts
|

Solar Open Flux Migration from Pole to Pole: Magnetic Field Reversal

Abstract: Coronal holes are solar regions with low soft X-ray or low extreme ultraviolet intensities. The magnetic fields from coronal holes extend far away from the Sun, and thus they are identified as regions with open magnetic field lines. Coronal holes are concentrated in the polar regions during the sunspot minimum phase, and spread to lower latitude during the rising phase of solar activity. In this work, we identify coronal holes with outward and inward open magnetic fluxes being in the opposite poles during sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The second is equatorward migration of coronal hole flux and OSF from both poles in the subsequent rising phase of the next cycle. The latter has been seen in studies using PFSS modelling (Wang and Sheeley, 1994;Bilenko and Tavastsherna, 2016;Huang et al, 2017) and also in studies of coronal hole distributions seen in infra-red maps and using fulldisk magnetograms to determine the field polarity (Bilenko, 2002). This pole-to-pole migration takes place simultaneously for the two polarities at different longitudes.…”
Section: Changes In the Spatial Distribution Of Osf Over The Sunspot ...mentioning
confidence: 78%
“…The second is equatorward migration of coronal hole flux and OSF from both poles in the subsequent rising phase of the next cycle. The latter has been seen in studies using PFSS modelling (Wang and Sheeley, 1994;Bilenko and Tavastsherna, 2016;Huang et al, 2017) and also in studies of coronal hole distributions seen in infra-red maps and using fulldisk magnetograms to determine the field polarity (Bilenko, 2002). This pole-to-pole migration takes place simultaneously for the two polarities at different longitudes.…”
Section: Changes In the Spatial Distribution Of Osf Over The Sunspot ...mentioning
confidence: 78%
“…Our results indicate that these CHs without OP1 are on average smaller and less unipolar than the CHs with open magnetic field lines. Such coronal holes are unlikely to be the source regions of high-speed solar winds, and can be one reason for the low consistency level between CHs and high-speed solar wind source regions reported by Huang et al (2017).…”
Section: Discussionmentioning
confidence: 93%
“…However, more recent studies have shown significant inconsistency between the CHs and the source regions of high-speed solar wind (e.g., Huang et al 2017), and between CHs and OMF regions (e.g., Obridko & Shelting 1999;Lowder et al 2014Lowder et al , 2017Linker et al 2017;Huang et al 2017Huang et al , 2019. Part of the inconsistency can be caused by methodological inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that these CHs without OP1 are on average smaller and less unipolar than the CHs with open magnetic field lines. Such CHs are unlikely to be the source regions of high-speed solar winds and can be one reason for the low consistency level between CHs and high-speed solar wind source regions reported by Huang et al (2017).…”
Section: Discussionmentioning
confidence: 93%
“…However, more recent studies have shown significant inconsistency between the CHs and the source regions of high-speed solar wind (e.g., Huang et al 2017) and between CHs and OMF regions (e.g., Obridko & Shelting 1999;Lowder et al 2014;Huang et al 2017;Linker et al 2017;Lowder et al 2017;Huang et al 2019). Part of the inconsistency can be caused by methodological inaccuracy.…”
Section: Introductionmentioning
confidence: 99%